2014
DOI: 10.7739/jkafn.2014.21.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Patient Safety Risk Factors and Safety Management by Nurses in Emergency Service, Hospitals*

Abstract: This was a descriptive research study to examine the patient safety risk factors and the level of safety management of nurses in emergency service, hospitals and to analyze the relationship between the two factors. Method: Data for analysis were collected from 232 nurses in emergency service, hospitals in Busan and Gyeongnam from July 30 to September 7, 2013. Data were analyzed using descriptive statistics, t-test, one-way ANOVA, and Pearson correlation coefficients. Results: Therapeutic agents showed the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The study [14] focusing on the relationship between ER nurses' awareness of patient safety and safe nursing practice, revealed that the higher nurses' awareness are especially about their hospital environment and management team, the higher progress of the safety activity. In study [17], ER nurses' awareness about patient safety risk, the higher safe nursing practice, and, study [26] reported that because safety management activity is highly influenced by the internal communication of the organization, efforts should be taken to improve communication between organizational members. Based on the previous research reports, there are various factors influencing the safe nursing practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study [14] focusing on the relationship between ER nurses' awareness of patient safety and safe nursing practice, revealed that the higher nurses' awareness are especially about their hospital environment and management team, the higher progress of the safety activity. In study [17], ER nurses' awareness about patient safety risk, the higher safe nursing practice, and, study [26] reported that because safety management activity is highly influenced by the internal communication of the organization, efforts should be taken to improve communication between organizational members. Based on the previous research reports, there are various factors influencing the safe nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergency department is especially vulnerable for patient safety, it is important for the ER nurses to seek ways to improve the safety of patients in their care. Until recently, many researches focusing on the safety of the ER patients have been done identifying the risk factors threatening patients' safety in the emergency department [5,17], ER nurses' safety awareness and management activities to promote the culture of patient safety [18][19], and proposal of safety measures to promote patient safety [20]. Although many previous studies focusing on the intensifying patient safety management activities exist, research studies focusing on the extent of safety of nursing care activities or analysis of nurses' perception of the importance of safe nursing care practices are hard to find.…”
Section: Introductionmentioning
confidence: 99%
“…These criteria were determined based on previous studies (KTAS Committee, 2021; Oh, 2017) that reported that at least 1 year of experience working in an emergency room was required for personnel in charge of emergency patient triage to demonstrate competence (KTAS Committee, 2021; Oh, 2017). Also, we included nurses without triage experience because triage continues from the patients' visit to the moment of discharge from the emergency room (Yun & Park, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Triage does not end in the pre-examination room but continues in the emergency room. Nurses must continuously monitor patients and re-evaluate changes in their status (Yun & Park, 2014). This study identified that when participants' work-related stress was high, their triage competence was high.…”
Section: Ta B L E 4 Factors Affecting Triage Competence (N = 156)mentioning
confidence: 99%
“…Since the emergency department is especially vulnerable for patient safety, it is important for the ER nurses to seek ways to improve the safety of patients in their care. Until recently, many researches focusing on the safety of the ER patients have been done identifying the risk factors threatening patients' safety in the emergency department [5,8], ER nurses' safety awareness and management activities to promote the culture of patient safety [9][10], and proposal of safety measures to promote patient safety [11]. Although many previous studies focusing on the intensifying patient safety management activities exist, research studies focusing on the extent of safety of nursing care activities or analysis of nurses' perception of the importance of safe nursing care practices are hard to find.…”
Section: Introductionmentioning
confidence: 99%